Health insurance in Nigeria: Findings from the People’s Voice Survey - Kevin Croke; Chike Nwangwu; Olufunke Bamidele Fasawe; Ifeyinwa Aniebo; Karima Ladhani; Margaret E. Kruk; Oyebanji Filani (PLOS Global Public Health, 2026)
The recent Lancet Commission on Nigeria’s health system highlighted high out of pocket expenditures on health and underfunding of the public health sector as major obstacles to Nigeria’s achievement of the Sustainable Development Goals. Nigeria has sought to address these gaps by extending health insurance coverage. This paper measures health insurance coverage and access to care in Nigeria in 2023, using the first round of the People’s Voice Survey. We analyze health insurance coverage by calculating coverage rates and using multivariate logistic regression to estimate associations between insurance coverage, socioeconomic characteristics, and health system utilization. In 2023, 2% of Nigerians had insurance from the National Health Insurance Scheme. Education and income were the most consistent predictors of insurance coverage. Chronic illness and self-reported health were not associated with insurance status. Respondents with insurance were less likely to use public sector primary care providers as their usual source of care, and were more likely to use private hospitals. Those with insurance were also more likely to have had an inpatient hospitalization in the preceding year, and more likely to have received key preventive screenings. While those with insurance receive more and better care in Nigeria, insurance access has been limited to relatively advantaged population groups. Mobile phone-based monitoring platforms such as the People’s Voice Survey could help policymakers in Nigeria track insurance coverage, and whether it contributes to reversal of these trends over time.